Neuromodulatory effect of the combination of metformin and vitamin D3 triggered by purinergic signaling in type 1 diabetes induced-rats. (1st March 2023) - Pereira, Aline da Silva; Miron, Vanessa Valéria; Castro, Milagros Fanny Vera; Bottari, Nathieli Bianchin; Assmann, Charles Elias; Nauderer, Jelson Norberto; Bissacotti, Bianca Fagan; Mostardeiro, Vitor Bastianello; Stefanello, Naiara; Baldissarelli, Jucimara; Palma, Taís Vidal; Morsch, Vera Maria Melchiors; et al.
Abstract: Several studies have indicated the vitamin D deficiency in the development of macro- and microvascular complications of diabetes mellitus (DM) including DM-related cognitive dysfunction. The purinergic system plays an important role in the modulation of a variety of mechanisms, including neuroinflammation, plasticity, and cell-cell communication. In addition, purines, their receptors, and enzymes can regulate the purinergic axis at different levels in type 1 DM (T1DM). This study evaluated the effects of vitamin D3 alone or in combination with metformin in the behavioral performance of streptozotocin-induced T1DM rats. The effects of this combination on the metabolism of ATP and ADP were also studied by NTPDase (CD39), AMP by 5′-nucleotidase (CD73), and adenosine by adenosine deaminase (E-ADA) in the brain and peripheral lymphocytes of type 1 diabetic STZ-induced rats. The results showed that anxiety and memory loss from the DM condition reverted after 30 days of vitamin D3 treatment. Furthermore, the DM state affected systemic enzymes, with no effect on the central enzymes hydrolyzing extracellular nucleotides and nucleosides. Vitamin D3 treatment positively regulated ectonucleotidase (NTPDase and 5′-nucleotidase) activity, E-ADA, and the purinergic receptors as a mechanism to prevent oxidative damage in the cerebral cortex of T1DM rats. A neuroprotector effect of vitamin D3 through adenosine signaling was also observed, by regulating A1 and A2A receptors proteins levels. The present findings suggest that purinergic signaling through vitamin D3 modulation may be a novel alternative strategy for T1DM treatment, and may compensate for the negative changes in the central nervous system. Graphical abstract: Image 1 Highlights: Vitamin D3 impacts purinoreceptors of synaptosomes from the hippocampus and cerebral cortex of T1DM rats. Vitamin D3 modulates adenosine receptors in T1DM animals. Vitamin D3 decreases anxious behavior in T1DM animals. Vitamin D3 demonstrated neuroprotective and neuromodulatory effects via purinergic signaling in T1DM.